Effect of plant extracts and a disinfectant on biological parameters and pathogenicity of the fungus Beauveria bassiana (Bals.) Vuill. (Ascomycota: Cordycipitaceae) - Martins,C. C. (2016)
Abstract The fungus Beauveria bassiana is naturally found in poultry houses and causes high rates of mortality in Alphitobius diaperinus. Laboratory and field experiments have shown the potential of this fungus as an insect control agent. However, in poultry houses, bacteria as Salmonella, can be found and have been studied alternative control methods for this pathogen. Thus, this study aimed to evaluate the effect of plant extracts and a disinfectant on the fungus Beauveria bassiana (strain Unioeste 4). Conidial viability, colony-forming unit (CFU) counts, vegetative growth, conidia production, insecticidal activity of the fungus and compatibility were used as parameters in the evaluation of the effect of these products on the fungus. Alcoholic and aqueous extracts of jabuticaba (Myrciaria cauliflora (Mart.), guava (Psidium guajava (L.)), and jambolan (Syzygium cumini (L.), at concentrations of 10% as well as the commercial disinfectant, Peroxitane® 1512 AL, were evaluated at the recommended concentrations (RC), 1:200 (RC), 0.5 RC and 2 RC. There was a negative influence of alcoholic and aqueous extracts of jabuticaba, guava and three dilutions of Peroxitane on the viability of conidia. The CFUs and vegetative growth of the fungus were affected only by the Peroxitane (all dilutions). For conidial production, the aqueous extract of guava had a positive effect, increasing production, while the Peroxitane at the R and RC concentrations resulted in a negative influence. The mortality of A. diaperinus, caused by the fungus after exposure to these products, was 60% for the peracetic acid at 0.5 RC, and above 80% for the extracts. Thus, the results showed that all the extracts and Peroxitane at RC 0.5 are compatible with the fungus B. bassiana Unioeste 4, however only the extracts had a low impact on inoculum potential.